Surface design of core-shell superparamagnetic iron oxide nanoparticles drives record relaxivity values in functional MRI contrast agents - Maity, Dipak; Zoppellaro, Giorgio; Sedenkova, Veronika; Tucek, Jiri; Safarova, Klara; Polakova, Katerina; Tomankova, Katerina; Diwoky, Clemens; Stollberger, Rudolf; Machala, Libor; Zboril, Radek (Chemical communications (Cambridge, England), 2012)
Core-shell hydrophilic superparamagnetic iron oxide (SPIO) nanoparticles, surface functionalized with either terephthalic acid or 2-amino terephthalic acid, showed large negative MRI contrast ability, validating the advantage of using low molecular weight and π-conjugated canopies for engineering functional nanostructures with superior performances.
Keywords: magnetická rezonanční tomografie; myši; povrchové vlastnosti; buňky NIH 3T3; Magnetic Resonance Imaging; NIH 3T3 Cells; Surface Properties; kontrastní látky; Contrast Media; Magnets; železité sloučeniny; zvířata; racionální návrh léčiv; Drug Design; Mice; Ferric Compounds; magnety; Animals